The University as a Platform for Discussions on the Ethical Aspect of Researchers’ Creativity - Korobko, Margaryta (Ukrainian Cultural Studies, 2023)
Creativity is very important for scientists, but, unfortunately, it rarely becomes a topic for discussion within the field of professional ethics of scientists, engineers, physicists, and other figures in science and technology. After all, creativity is often considered a prerogative of artists only, and in this aspect, the moral side of creativity is practically not discussed. The purpose of the article is to show the importance of the moral aspect of creativity and the role of the university in understanding this. General scientific methods were used in the article: analytical, comparative, and generalization. Common from a public perspective is to think about science and technology in terms of the pervasive and ubiquitous practical impact of scientific achievements: electrification, cars, airplanes, water supply, computers, etc. However, to assess the societal impact of science and technology we cannot neglect the moral importance of scientific knowledge itself and the personal commitments of scientists, engineers, and other science-oriented professionals. Personal commitments and ideals include humanitarian, environmental, religious, political, aesthetic, and family obligations. They also include voluntary commitments to adhere the professional standards, especially when these commitments are related to a person’s broader value perspective. The university promotes not only the development of scientific creativity among students but also an opportunity to understand the moral problems of their professional activities and obtain possible solutions to these problems in professional and corporate ethics courses. Thus, the university helps students in their future activities as the first platform for discussions on the ethical aspect of researchers’ work.